A New Approach For Production Scheduling In Open-Pit Mines - Y. G. Zhang (Society for Mining, Metallurgy & Exploration, 1986)
Interactive Dynamic Optimization Method (IDOM) will be presented in this paper. IDOM combines inventory theory, dynamic programming, computer simulation and interactive technique to formulate a production schedule for open-pit mines. This new method has been successfully used in metal mines of China for years.